The rate of technical change in Finnish agriculture, 1960 to 1990 - Sims, Eric N. (Agricultural Research Centre of Finland, 1994)
Edellinen laaja tutkimus Suomen maataloustuotannon tuottavuudesta käyttäen indeksilukuja valmistui 1970. Duaaliteoriaa ja joustavia funktiomuotoja on kehitetty merkittävästi mainitun tutkimuksen jälkeen. Samoin indeksilukujen ja tuotantoteknologioiden välisessä riippuvuussuhteessa tapahtuneen kehityksen ansiosta on voitu määritellä tietty määräindeksi kaikkia muita paremmaksi. Tässä tutkimuksessa sovellettiin uusia tuottavuuden mittaamistekniikkoja Suomen maataloustuotannon tuottavuuden kasvun selvittämiseksi vuosien 1960 ja 1990 välisenä aikana. Keskimääräinen vuosittainen teknisen muutoksen nopeus oli tutkimusajanjaksona 3,6 %. Muutosvauhti on hieman suurempi kuin vastaavat luvut Iso-Britanniasta ja Irlannista.

The last major study of the productivity of Finnish agriculture using index numbers was completed in 1970. Since that study, there have been significant advances in duality theory and flexible functional forms. Similarly, the progress in the relationship between specific index numbers and production technologies has allowed a specific quantity index to be termed 'superlative.' The new techniques of measuring productivity are applied here to examine intertemporal productivity growth in Finnish agriculture from 1960 to 1990. During the period examined, the average annual rate of technical change is 3.6%. This rate is slightly greater than those reported for the U.K. and Ireland.
Keywords: Ma; Suomi; tuottavuus; Finland; productivity; index numbers; technical change